Pilot Evaluation of a Tablet-Based Application to Improve Quality of Care in Child Mental Health Treatment. Issue 2 (March 2019) - Davidson, Tatiana M.; Bunnell, Brian E.; Saunders, Benjamin E.; Hanson, Rochelle F.; Danielson, Carla K.; Cook, Danna; Chu, Brian C.; Dorsey, Shannon; Adams, Zachary W.; Andrews, Arthur R.; Walker, Jesse H.; Soltis, Kathryn E.; et al.
Abstract: Mental health systems need scalable solutions that can reduce the efficacy–effectiveness gap and improve mental health outcomes in community mental health service settings. Two major challenges to delivery of high-quality care are providers' fidelity to evidence-based treatment models and children's and caregivers' engagement in the treatment process. We developed a novel, tablet-based application designed to enhance via technology the quality of delivery of trauma-focused cognitive-behavioral therapy (TF-CBT). We piloted its use in four community mental health service organizations using a blocked randomized controlled trial to examine the feasibility of implementing tablet-facilitated TF-CBT versus standard TF-CBT with 13 providers and 27 families. Provider fidelity and child engagement in treatment were observationally measured via session audio recording. Parent and child perceptions of the tablet application were assessed using structured interviews and mixed-method analyses. Providers actively and appropriately used tablet TF-CBT to facilitate treatment activities. Providers and families expressed high satisfaction with its use, demonstrating acceptability of this approach. Youth and caregivers in both conditions reported high alliance with their providers. Overall, we found that tablet-facilitated treatment is accepted by providers and families and may be integrated into mental health treatment with minimal training. Further study is needed to examine the extent to which technology-based applications may enhance the reach, quality, and clinical outcomes of mental health treatment delivered to children and families. Highlights: Evaluated the feasibility of tablet-facilitated trauma-focused CBT Provider fidelity and child engagement were measured via session audio recording Providers and families expressed high satisfaction with tablet trauma-focused CBT